A Disulfide-Bonded Dimer of the Core Protein of Hepatitis C Virus Is Important for Virus-Like Particle Production - Kushima, Yukihiro (American Society for Microbiology (ASM), 2010)
Hepatitis C virus (HCV) core protein forms the nucleocapsid of the HCV particle. Although many functions of core protein have been reported, how the HCV particle is assembled is not well understood. Here we show that the nucleocapsid-like particle of HCV is composed of a disulfide-bonded core protein complex (dbc-complex). We also found that the disulfide-bonded dimer of the core protein (dbd-core) is formed at the endoplasmic reticulum (ER), where the core protein is initially produced and processed. Mutational analysis revealed that the cysteine residue at amino acid position 128 (Cys128) of the core protein, a highly conserved residue among almost all reported isolates, is responsible for dbd-core formation and virus-like particle production but has no effect on the replication of the HCV RNA genome or the several known functions of the core protein, including RNA binding ability and localization to the lipid droplet. The Cys128 mutant core protein showed a dominant negative effect in terms of HCV-like particle production. These results suggest that this disulfide bond is critical for the HCV virion. We also obtained the results that the dbc-complex in the nucleocapsid-like structure was sensitive to proteinase K but not trypsin digestion, suggesting that the capsid is built up of a tightly packed structure of the core protein, with its amino (N)-terminal arginine-rich region being concealed inside.